Masticatory muscle tendon-aponeurosis hyperplasia: clinical presentation and management - Al Qattan Ahmed; Al Hashmi Ahmed; Al Rashdi Said (EDP Sciences, 2022)
Introduction: Masseter muscle enlargement accompanied by hypertrophy of Mandibular angle can significantly affect the appearance and quality of life. The treatment methods can be varied, and, in the present study, osteotomy of Mandibular angle and treatment of Masseter muscle with Botulinum toxin was carried out. Observation: In this case study, a 19-year-old female patient was admitted with inadequate mouth opening for three years. Clinical examination and Cone-Beam Computed Tomography scan revealed bilateral well-developed Masseter muscles and hypertrophy of mandibular angle on both sides. Osteotomy of mandibular angle was performed. Additionally, 25 units of Botulinum toxin were administered. This improved the aesthetic appearance and increased the mouth opening from 21 mm to 38 mm in one year after surgery. Conclusion: Oral and maxillofacial surgeons should consider Masticatory muscle tendon-aponeurosis hyperplasia as a differential diagnosis when the patient's chief complaint is inadequate mouth-opening with a square mandible. Osteotomy of mandibular angle in conjunction with, Botulinum toxin is efficient in cases of Masseter muscle hypertrophy and an enlargement of the Mandibular angle.